Fe3O4 Nanoparticles for Complex Targeted Delivery and Boron Neutron Capture Therapy - Dukenbayev, Kanat; Korolkov, I. V.; Tishkevich, Dania; Kozlovskiy, Artem; Trukhanov, Sergey; Gorin, Yevgeniy; Shumskaya, Elena; Kaniukov, E. Yu.; Vinnik, Denis; Zdorovets, M. V.; Anisovich, Marina; Trukhanov, Alex; et al. (MDPI, 2019)
Magnetic Fe3O4 nanoparticles (NPs) and their surface modification with therapeutic substances are of great interest, especially drug delivery for cancer therapy, including boron-neutron capture therapy (BNCT). In this paper, we present the results of boron-rich compound (carborane borate) attachment to previously aminated by (3-aminopropyl)-trimethoxysilane (APTMS) iron oxide NPs. Fourier transform infrared spectroscopy with Attenuated total reflectance accessory (ATR-FTIR) and energy-dispersive X-ray analysis confirmed the change of the element content of NPs after modification and formation of new bonds between Fe3O4 NPs and the attached molecules. Transmission (TEM) and scanning electron microscopy (SEM) showed Fe3O4 NPs’ average size of 18.9 nm. Phase parameters were studied by powder X-ray diffraction (XRD), and the magnetic behavior of Fe3O4 NPs was elucidated by Mössbauer spectroscopy. The colloidal and chemical stability of NPs was studied using simulated body fluid (phosphate buffer—PBS). Modified NPs have shown excellent stability in PBS (pH = 7.4), characterized by XRD, Mössbauer spectroscopy, and dynamic light scattering (DLS). Biocompatibility was evaluated in-vitro using cultured mouse embryonic fibroblasts (MEFs). The results show us an increasing of IC50 from 0.110 mg/mL for Fe3O4 NPs to 0.405 mg/mL for Fe3O4-Carborane NPs. The obtained data confirm the biocompatibility and stability of synthesized NPs and the potential to use them in BNCT.
https://www.ncbi.nlm.nih.gov/pmc/articles/PMC6523109/
Keywords: magnetic nanoparticles; iron oxide; surface functionalization; APTMS; carborane